Transformational leadership in practice: bridging the chasm - Salem, Tarek; Thomson, Stanley Bruce (My University, 2023)
This chapter captures the bi-furcated challenge of implementing the transformational leadership practices in a complex organizational context. The authors embark on Bass' 4I transformational leadership model and suggest a variety of imperative skills necessary for the proper implementation. From the suggested pool of skills, two are highlighted as the most important and resonate with the 4I model. These are creativity and innovation skills and change management skills. The authors expect to find out the importance of transformational leaders to empower and enable the second line of operational leaders that are capable of efficiently and effectively bridging the transformational leadership chasm from the leaders' vision to the followers' practice.
Keywords: transformational leadership; management; leadership